Determining the bond characteristics of 7.5-mm and 7.8-mm prestressing wires - McMillan, Evan Ryan (Kansas State University, 2023)
A study was conducted to investigate the bond properties of three different types of large-diameter chevron-indented prestressing wires. Nine 6”x10” beams were cast for each type of wire at lengths of 5.5-ft, 6.5-ft, and 7.5-ft. The Type III concrete mixture used was kept constant throughout the study to investigate the effects of the wire profile and concrete release strength on bond behavior. During beam fabrication, prestressing reinforcement was gradually detensioned when concrete compressive strengths reached 3,500 psi, 4,500 psi, and 6,000 psi. To better understand the bond properties of each wire and to evaluate the effect of differing concrete release strengths on bond, prestressing wire end-slip measurements and concrete surface displacement measurements were made on all beams immediately after detensioning, 1-week after detensioning, and prior to flexural testing. Transfer lengths for each specimen were then determined from the plotted values of surface strain. All 27 beams were tested under three-point bending to determine the development lengths for each specimen. Results from the data obtained in this study were then used to compare bonding properties, assess accuracy of current equations for transfer and development length, and develop equations to predict transfer length and development length in members manufactured with the large-diameter indented prestressing wire used in this research.
Keywords: Prestressing wire; Transfer length; Bond; Development length; Indented wire